Transitabilidad Peatonal En Un Trecho De La Vía España Con Edificios Con Espacios De Transición: Cañón Urbano Entre Plaza Regency Y El Rey (Global Journals of Research in Engineering, 2023)
The walkability was studied in the urban canyon of the V a Espa a in Panama City between the Rey Supermarket the pedestrian bridge Plaza Concordia and Plaza Regency The pedestrian analysis was based on the multivariate logic model It was carried out with two cameras simultaneously filming both sides of the urban canyon of the Via Espa a in a period of one hour from 12 30 pm to 1 30 pm from July 5 2018 with the aim of quantifying the routes and deviations of pedestrians 60 of the pedestrians passed through the transition spaces of the Plaza Regency sector and at the Rey supermarket sector 85 of the pedestrians used the transition spaces of the building In Plaza Regency pedestrians make small deviations to walk within the shaded area transition space however in the Rey supermarket sector the flow of pedestrians has a continuous and well-defined path
Keywords: walkability; pedestrian comfort; activity mapping; deviation; perception of the environment; route choice; urban canyon